Agresivno vedenje v procesu dolgotrajne rehabilitacije po pridobljeni možganski poškodbi - Šemrov, Maša (Psihološka obzorja (Ljubljana), 2020)
Aggressive behaviour that follows acquired brain injury (ABI) is often hampering successful re-integration into the social life wherein causes and types vary. We focus on the consequences of ABI which are associated with the occurrence of aggressivebehaviour and also hamper its treatment in the process of long-term rehabilitation. Specifically, we analyse changes in inhibitory control, reduced self-awareness, problems with accepting the situation and consequent emotional issues, and changes in personality and behaviour. In the process of long-term rehabilitation, we use an individually tailored approach, which aims to support and enable a person with ABI to develop more effective ways to cope with disabilities. As the outcomes in terms of progress are limited to specific situations, it is unlikely that aggressive behaviour would not repeat. We nevertheless find that knowledge of this phenomenon may reduce the frequency of aggressive behaviour and its impact on everyday functioning.
Keywords: acquired brain injury ABI; aggressive behavior; agresivno vedenje; health psychology; pridobljena možganska poškodba PMP; rehabilitacija; rehabilitation; treatment; zdravljenje; zdravstvena psihologija